Efficient symmetrical electrodes based on LaCrO3 via microstructural engineering. - Zamudio-García, Javier; Porras-Vázquez, José Manuel; Ramírez-Losilla, Enrique; Marrero-López, David (Elsevier, 2021)
Novel nanostructured electrodes, La0.98Cr0.75B0.25O3δ (B = Mn, Fe, Ti and Cu), are prepared by a single spraypyrolysis deposition method directly on the electrolyte and a porous Ce0.9Gd0.1O1.95 (CGO) scaffold. These perovskite-type electrodes without alkaline-earth metals exhibit low ionic/electronic conductivity; however, the polarization resistance is greatly enhanced by microstructural design. The best results are obtained for La0.98Cr0.75Mn0.25O3-δ deposited into a porous CGO-scaffold due to the synergetic effect of CGO, with high ionic conductivity, and doped-LaCrO3 with a predominantly electronic conductivity. The materials are investigated as both air and fuel electrodes for solid oxide fuel cells (SOFCs) by different structural, microstructural and electrochemical techniques. Low values of polarization resistance are achieved for nanostructured La0.98Cr0.75Mn0.25O3-δ-CGO electrodes, i.e. 0.057 Ω cm2 in air at 800 ◦C, compared to 0.96 Ω cm2 for the same powder electrode obtained by screen-printing deposition. An electrolyte-supported symmetrical cell generates a stable maximum power output of 475 mW cm􀀀 2 at 800 ◦C.
Keywords: Pilas de combustible; Electroquímica; Spray-pyrolysis; Symmetrical solid oxide fuel cells